Global increase of SF6 observed in the atmosphere - Maiß, Manfred; Levin, Ingeborg (Universitätsbibliothek der Universität Heidelberg, 1994)
High precision long-term observations of the trace gas sulphur hexafluoride (SF6) in background air at Neumayer station, Antarctica (1986-1991), and at Izana observatory, Tenerife (1991-1992), are presented. Since the very first measurements in 1970 (0.03pptv), the purely anthropogenic greenhouse gas SF6 has increased by two orders of magnitude to a global mean value of 2.8pptv in 1992. The observations can best be fitted by a quadratic curve with a recent increase rate of 8.3%/yr. A significant north-south gradient of 0.29pptv is observed. From this gradient an interhemispheric exchange time of 1.4 years is derived. A modeled atmospheric budget history agrees reasonably well with estimates of global SF6 production rates and leads to an extrapolated SF6 concentration of about 20pptv for the year 2030.
Wissenschaftl. Aufsatz. - Aus: Geophysical Research Letters